FEATURES OF THE CONTENT OF CORPORATE CONTRACTS - E. P. Gladneva; Y. P. Praslov (Russian Journal of Economics and Law)
Objective: to study the legal nature, to reveal the peculiarities of the subject and other essential terms of corporate contracts as a technique and means of legal regulation of corporate relations. Methods: general and specific methods of cognition: dialectical, formal logic (analysis, synthesis, modeling), structural and systemic-functional methods, as well as comparative legal, logical, legal, historical, legal, grammatical methods and systemic interpretation. Results: it is concluded that the object of corporate contracts includes terms about the features of implementation of corporate rights for shares and share in capital assets; conditions (order) of the implementation of corporate rights and approval of other actions related to company management, activity, reorganization and liquidation; the passive duty of corporate organizations to refrain from committing any action (authority), arising from the nature of corporate agreements, as well as the active responsibilities associated with the certain implementation of corporate rights, certified by stocks (shares), rights to stocks (shares). In addition to the subject, the content of corporate contractsincludes other essential (necessary) conditions stipulated by the corporate legislation norms and the agreement of the participants of economic entity. Scientific novelty:for the first time, taking into account modern achievements of civilistic jurisprudence and practice, the authors investigate the relationship between the concepts of a civil contract and corporate contract, give the definition of corporate contract, show the specificity of the subject and other material terms of corporate contracts. Practical significance: the findings can be taken into account in the further research of corporate law issues as sub-branch of civil law, used in law making and enforcement activities, in the educational process as a teaching material in civil law.